2005
DOI: 10.1111/j.1442-200x.2005.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever in a childhood population in eastern Turkey

Abstract: It was noted that the FMF patients in this study had a broad spectrum of mutation combination, which might reflect the intercultural interactions of ancient ethnic groups that lived in Anatolia, and these mutations were not significantly different in respect to clinical presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
6
28
2
3
Order By: Relevance
“…In other studies, the prevalence of M694V mutation was reported as 48%, 71.3% and 74.3%, respectively (Yilmaz et al 2001;Ertekin et al 2005;Inal et al 2008). Phenotype and genotype correlation in FMF has not been explained definitely, but an increased risk of amyloidosis among M694V homozygotes was reported (Paut et al 2000;Yilmaz et al 2003;Dusunsel et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…In other studies, the prevalence of M694V mutation was reported as 48%, 71.3% and 74.3%, respectively (Yilmaz et al 2001;Ertekin et al 2005;Inal et al 2008). Phenotype and genotype correlation in FMF has not been explained definitely, but an increased risk of amyloidosis among M694V homozygotes was reported (Paut et al 2000;Yilmaz et al 2003;Dusunsel et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…A large part of these manifestations may be directly related to FMF, its complications, associated diseases, and treatment adverse effects. 3 Ertekin et al 10 described seizures in two of 52 children with FMF. While one of the patients with seizures had electroencephalography abnormality, the other was considered as simple febrile convulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Our series (FMF cases in renal waiting list) at this moment is not large, so it is difficult to make evaluation between genotype of patients and amyloidosis. There is regional study performed on pediatric group reported that M694V mutation is the most common one [10].…”
Section: Discussionmentioning
confidence: 99%